Les usages de la laïcité : une comparaison École-Hôpital - Geneviève Zoïa; Laurent Visier
This article proposes to compare the genesis and uses of secularism in two major socialization institutions, school and hospital. We show that secularism, though historically thought of in both institutions as simultaneously producing integration and emancipation, society and subject, collective and individual, is today mobilized in a very different way by the respective actors, professionals and users, of these institutions. After having first shown the relevance of a comparison, we will then look at the uses and manifestations of secularism at school and hospital. Finally, we will conclude with explanations of these differences.